2000
DOI: 10.1212/wnl.54.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lidocaine in central pain

Abstract: Systemic lidocaine can induce a significant and selective reduction of several components of pain caused by CNS injuries. The observed preferential antihyperalgesic and antiallodynic effects of this drug suggest a selective central action on the mechanisms underlying these evoked pains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(157 citation statements)
references
References 40 publications
3
147
0
7
Order By: Relevance
“…Lidocaine, an intravenously administered analgesic drug, was shown to be effective in treating post-SCI pain, [51][52][53] with one exception. 55 The one exception may be due to the fact the study's authors used only half the dosage seen in the other studies with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine, an intravenously administered analgesic drug, was shown to be effective in treating post-SCI pain, [51][52][53] with one exception. 55 The one exception may be due to the fact the study's authors used only half the dosage seen in the other studies with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Following the lidocaine injections, 13 patients reported a significant mean reduction in pain from baseline averaging 2 hours when compared to placebo (p<0.01). Attal et al, 52 reported on 15 patients who received lidocaine intravenously and experienced a greater reduction in pain than those who received placebo, with an effect lasting up to 45 minutes post injection, and a reduction in the intensity of brush-induced allodynia and mechanical hyperalgesia. In a RCT study by Finnerup et al, 53 those patients who received lidocaine intravenously (n=24) in two treatment sessions 6 days apart reported significantly less pain than those who did not receive lidocaine.…”
Section: Analgesics For Sci Painmentioning
confidence: 99%
“…For both at-level and below-level neuropathic pain, we suggest that first-line treatment is systemic lignocaine, [16][17][18] in the acute, in-patient setting and gabapentin [19][20][21] in the subacute or chronic setting. If gabapentin fails to provide adequate relief, we would suggest the use of a tricyclic antidepressant such as amitriptyline or nortriptyline or a weak opioid such as tramadol as a second-line treatment.…”
Section: At-level and Below-level Neuropathic Painmentioning
confidence: 98%
“…[62][63][64] One trial also included patients with stroke. 63 Two of the studies found a significant reduction in pain intensity with intravenous lidocaine compared with placebo, 62,63 whereas the third found no significant difference.…”
Section: Intravenous Lidocainementioning
confidence: 99%